2019
DOI: 10.3390/coatings9100634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Temperature on the Optical and Electrical Properties of Nitrogen-Doped NiO Thin Films

Abstract: NiO is a widely used p-type semiconductor. The desired optical and electrical properties of NiO vary in different application fields. To modulate the properties of NiO, nitrogen (N)-doped NiO thin films were synthesized by reactive radio-frequency magnetron sputtering on ITO-coated glass substrates. The influence of substrate temperature on the properties of NiO was investigated. XRD studies indicated a cubic structure. With the increase of the substrate temperature, the average transmittance in the visible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
0
5
1
Order By: Relevance
“…The lessdisordered structure and the decrease in the tensile strain of NiO upon nitrogen doping resulted in more transparent films with a larger energy gap. These observations are not in accordance with theoretical predictions [19] and published experimental work [32,[37][38][39][40] for nitrogen-doped NiO, which are presented in Table 1. This is attributed to the quality and stoichiometry of the undoped NiO fabricated by sputtering in this work, such as the preferential growth of crystallites in the (200) direction instead of the (111) generally observed and the high ratio of at.% O/N~1.72.…”
Section: Nio:n Thin Filmscontrasting
confidence: 62%
See 2 more Smart Citations
“…The lessdisordered structure and the decrease in the tensile strain of NiO upon nitrogen doping resulted in more transparent films with a larger energy gap. These observations are not in accordance with theoretical predictions [19] and published experimental work [32,[37][38][39][40] for nitrogen-doped NiO, which are presented in Table 1. This is attributed to the quality and stoichiometry of the undoped NiO fabricated by sputtering in this work, such as the preferential growth of crystallites in the (200) direction instead of the (111) generally observed and the high ratio of at.% O/N~1.72.…”
Section: Nio:n Thin Filmscontrasting
confidence: 62%
“…It is seen that the structural defects of the as-prepared NiO film created states in the band gap resulting in a decrease in transmittance and a very slow rate of increase in absorption coefficient (also shown in Figure 2c) as photons with increasing energy are impinging on the film surface. It has been reported that Ni +2 vacancies create Ni +3 and in association with the stress and the defects of the structure (interstitial oxygen, boundaries of small grains-crystallites) can be responsible for the low visible transmittance [17,18,40,44] and the relatively low energy band gap (3.15 eV) of undoped NiO [17]. The optical properties of undoped NiO are discussed in more detail in conjunction with the properties of the nitrogen-containing NiO films in the next section.…”
Section: Properties Of Nio and Nio:nthin Films Nio Thin Filmsmentioning
confidence: 94%
See 1 more Smart Citation
“…This endorsed the presence of GO and MnO 2 in the composites [ 5 , 35 , 36 , 37 ]. In the case of Raman spectra for NGO, two significant peaks of GO representing D and G bands were assigned, and remaining broad peaks were observed at 488 cm −1 and 929 cm −1 and assigned to first order (1P) phonon, longitudinal optical and transverse optical mode (LO + TO) in NiO [ 22 , 29 , 38 , 39 , 40 , 41 ]. In the case of Raman spectra for NMGO, the peaks of MnO 2 , NiO, and GO were observed, which endorsed the successful formation of an NiO/MnO 2 /GO composite as shown in Figure 2 b.…”
Section: Resultsmentioning
confidence: 99%
“…The intense peaks at 853.9 eV and 872.8 eV are attributed to Ni 2+ while the other peak at 855.7 eV is ascribed to Ni 3+ . [48][49][50] The ratio of Ni 3+ increases with sputtering temperatures. Meanwhile, Fig.…”
mentioning
confidence: 99%